Indications and Outcomes of Mohs Micrographic Surgery Using a Multidisciplinary Approach: A Decade of Experience. Issue 1 (January 2021) - Wang, Weitao; Lee, Joseph; Qin, Shuyang; Brown, Marc D.; Doerr, Timothy
Abstract : BACKGROUND: Traditional approaches of staged outpatient Mohs Micrographic Surgery (MMS) in nonmelanoma skin cancer (NMSC) followed by reconstruction is not possible in a subset of patients. OBJECTIVE: Assess the indications and outcomes of a multidisciplinary approach MMS. METHODS AND MATERIALS: Retrospective, single-surgeon, single Mohs specialist, university-based tertiary care referral practice, including all MMS performed in the operating room setting with concurrent reconstruction in patients from 2008 to 2018 with minimum follow-up of 6 months. Patients with NMSCs who completed multidisciplinary MMS approach were included. Number of Mohs stages, duration of procedure, reconstruction techniques, and complications including flap loss, bleeding, hematoma, wound infections, dehiscence, and local recurrence rates were reviewed. RESULTS: Three hundred twenty patients were included, 160 male and 160 female with mean ages of 71.6 and 72.1 years, respectively. Indications for a multidisciplinary approach MMS were as follows: neuro/psych 22.5%, extensive anticipated defect size 55%, patient request/convenience 4.4%, medical intolerance 5%, multiple reasons 8.1%, and unknown in 5%. Average stage required to clear margins was 1.57 ± 0.64. Mean operative times by increasing Mohs stages up to 3 including reconstruction were 125.1, 159.3, and 195.5 minutes, respectively ( p < .00001). CONCLUSION: Indications for a multidisciplinary approach MMS were extensive defects and neuro/psych issues. Advantages include patient tolerance and single-stage procedure. Abstract : Supplemental Digital Content is Available in the Text.